THE UNDERSTANDING OF INTERNAL QUALITY ASSESSORS TOWARDS ASEAN UNIVERSITY NETWORK QUALITY ASSURANCE (AUN-QA) AT A PROGRAM LEVEL - Anuwong, Kunncadah; Supasuteekul, Ajaree; Yoonaisil, Waiyawut; Suppakarn, Nitinat; Damnui, Pinpinat; Sawatwipachai, Braprut (Srinakharinwirot University Journal of Sciences and Technology, 2022)
The objective of this study is to explore the understanding of internal quality assessors towards the AUN-QA criteria. Data were collected from 112 academic staff currently served as program internal assessors in 11 Thai universities by an in-depth interview during November 16 to December 25, 2017. These universities had implemented AUN-QA at a program level. The results show that all respondents received the training on AUN-QA criteria and assessment procedure prior to their first assessment. About 80% of them had an experience in assessing six to nine programs, with the number of two to five assessors per team. All respondents self-rated their understanding of AUN-QA criteria as “fair.” In addition,the respondents believed that the assessors should be trained more on the following issues, including the assessment of Expected Learning Outcomes (ELOs); the design of curriculum, teaching and learning activities, and student assessment to be aligned with ELOs; the calculation of lecturers’ workload according to AUN-QA; and the correct concept and procedure of need analysis and benchmarking.